Sex-based differences in program completion and clinical outcomes in patients following outpatient cardiac rehabilitation. (11th May 2021) - Chan, E; Chirico, D; Arena, R; Feng, Y; Liang, Z; Ahmed, SB; Colbert, J; Aggarwal, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Females have greater reduction in mortality compared to males, following completion of a cardiac rehabilitation (CR) program, yet they continue to have lower referral rates and program completion. Since 1996, a local rehabilitation program has been the main provider of CR in our health zone. A standardized rapid referral program was implemented in 2008 to improve referral rates of hospitalized patients. Since then, the relationship between sex and CR completion is unknown. Purpose: To evaluate the relationship between sex and CR completion and to evaluate the association between CR completion and clinical outcomes, stratified by sex. Methods: We included consecutive patients who were referred to CR and who: 1) were hospitalized for an acute coronary syndrome (ACS) or stable angina between 2008 and 2016; 2) had angiographic evidence of at least one-vessel coronary disease; and 3) had revascularization with percutaneous intervention, coronary artery bypass or medical management. The outcomes of interest were CR completion, anxiety and depression categories, exercise capacity, death, and need for revascularization. Logistics regression models were used to determine the association between sex and CR completion. The association between sex, CR completion, and the outcomes of interest were assessed using multivariable cox proportional hazards models. Results: A total of 726 females and 2645 males were included in this study. The rate of CR completion was lower in females compared to males (64.6% vs 69.98%, p = 0.006). Following adjustment for baseline characteristics, female sex independently predicted lower rates of CR completion, OR 0.81 (95%CI 0.67-0.97). Both sexes displayed improvements in peak metabolic equivalents (METs) achieved during exercise testing (W: initial 5.99 ± 1.93; 12-week 7.22 ± 1.92; M: initial 7.62 ± 2.04; 12-week 8.81 ± 1.93, p = 0.001). Amongst CR completers, one-year mortality was similar between sex (W: 1.84% vs M: 3.27%, p = 0.118), as was revascularization (W: 14.29% vs M: 11.97%, p = 0.193), however both sexes had higher one-year mortality in CR non-completers. Conclusion: Despite a standardized CR referral protocol, a sex-difference in CR completion remains. In CR completers, one-year mortality and revascularization was similar in both sexes, however mortality was higher in CR non-completers. Our study suggests that addressing the causes of female CR non-completion following ACS or stable angina may improve outcomes.